2013
DOI: 10.1007/s13191-013-0329-8
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on the Relationship Between Inter Alar Width, and Inter Commissural Width on Circumferential Arc Width of Maxillary Anterior Teeth in Different Age Groups

Abstract: This study was done to determine the relationship between interalar width and inter commissural width on circumferential arc width of maxillary anterior teeth in dentulous subjects between the age groups of 20-50 years. The study involved 300 subjects, in whom measurements were made from the distal aspect of each maxillary canine, across the facial surfaces of the six anterior teeth, using brass wire and a Vernier calliper. Interalar and inter commissural width were recorded after placing two points and measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
9
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 19 publications
5
9
2
Order By: Relevance
“…The observation regarding the combined mesiodistal width of maxillary anterior teeth in this present study in the males was slightly higher than in females though it was not statistically significant and is comparable to some previous studies. [19202126] The above concordance in the majority of the study confirms that the dimensions of body parts in males are higher than in females. [202122] There was a strong correlation between the ratio of circumference of head and mesiodistal width of the six anterior teeth which was statistically significant which is in accordance with the study by Rahamatulla et al .…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The observation regarding the combined mesiodistal width of maxillary anterior teeth in this present study in the males was slightly higher than in females though it was not statistically significant and is comparable to some previous studies. [19202126] The above concordance in the majority of the study confirms that the dimensions of body parts in males are higher than in females. [202122] There was a strong correlation between the ratio of circumference of head and mesiodistal width of the six anterior teeth which was statistically significant which is in accordance with the study by Rahamatulla et al .…”
Section: Discussionsupporting
confidence: 66%
“…[34510] In the present study, there was a statistically significant difference between the circumference of head measurements in the males and females ( P < 0.001). Previous studies[21222324] have reported a significant correlation between body height and head length, head width, as well as head circumference. Ilayperuma et al .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[29][30][31] Interalar width has been thus used extensively to select maxillary teeth in artifi cial prostheses. 29,[31][32][33] By and large, this hypothesis was rejected in current study for normal population (p<0.001). The discrepancy may be attributed to the measurement methods.…”
Section: Discussioncontrasting
confidence: 49%
“…Kurien et al . [ 11 ] on a study on 300 participants in Mangalore, India, also reported an average interalar width of 29.72 and 31.52 mm and 47.35 and 49.91 mm in females and males, respectively. The study concluded that the interalar distance showed significant relation to the width of six maxillary anterior teeth in the studied population.…”
Section: Discussionmentioning
confidence: 99%